Pengaruh Website Quality dan E–Satisfaction Terhadap E-Loyalty Pada Website pssi.org - Bambang Supriadi; Abdul Yusuf (COSTING : Journal of Economic, Business and Accounting, 2021)
This study aims to acknowledge any relationship between Website Quality and E - Website user satisfaction with E-Loyalty of website users. In this study the authors used quantitative research methods. The independent variable is the variable that affects or causes the change or the dependent variable arises. In this research, the independent variables are Website Quality and E - Satisfaction. The dependent variable on the variable which is the result of the effect, because the independent variable. The dependent variable in this research is E - Loyalty. The population in this study is online ticket buyers throughout Indonesia through the PSSI.org website, which is unlimited. The population is users of the PSSI Web Site throughout Indonesia. The sampling technique used in this study is a random sampling technique by presenting a total of 10-15% based on the population of buyers or users of the PSSI.org Web site throughout Indonesia which is provided unlimited, it is known The number of samples using the Jacob Cohen formula using an error level of 10% was obtained as many as 204 respondents. The results of the research obtained by the authors also partially Website Quality and E - Satisfaction has a significant effect on E - Loyalty on the PSSI.org Website, E - Satisfaction with E - Loyalty has a proportion value of 8.2%, Website quality has a higher effect on E - Loyalty on the PSSI.org Site with a proportion of 10.2%. Effect of Website Quality and E - Website user satisfaction on E - Website user loyalty simultaneously with an effect of 35.8%, while the remaining 64.2% is by other variables not examined in this study Keywords: Website Quality , E – Satisfaction , E – Loyalty